LEMBAGA AMIL ZAKAT NASIONAL (LAZNAS) YAYASAN NURUL HAYAT DALAM MELAKUKAN MANAJEMEN RISIKO REPUTASI - Nisrinah Arofahtus Sholehah; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this study is to find reputational risk management carried out by LAZNAS Nurul Hayat. The use of the method in this research used a qualitative approach through a case study. The main focus in this research is one of the risk that is classified in the International Working Group on Zakat Core Principle (IWGZCP) is reputational risk and the loss of muzakki of four of a kind which is one of the risk that owned by the management of zakat management institutions, besides the distribution of risk, operational risk, and zakat risk transfer among countries. The selection of focus reputation related risk is based on that important for a non-profit organization to having a good reputation of the institution to sustainability. The result of the research indicated that reputation risk management owned by nurul fountain of life begins with the concept of a reputation they believed, namely based on the system and performance. In the implementation, nurul fountain of life chosen to carry preventive measures ( prevention risk management ) related to reputation. Seven events are able to exert reputation hayat described related nurul derived from internal and external. Due to belief that the concept of reputation is related to performance and system, so focused prevention is done by the agency to minimize the possibility of internal events which consist of delay in overcoming complaint, late arrivals donations, less working spirit of employees, disobedience to SOP, inadequate accountability and inappropriate beneficiaries of granted aid. The results showed that external factors have no significant effect on the reputation of the institution.Keywords: zakat, risk management, reputation risk, LAZNAS Nurul Hayat FoundationREFERENCES A.B.Susanto, Himawan Wijarnako. 2004. Power Branding : Membangun Merek Unggul dan Organisasi Pendukungnya. Quantum Bisnis&Manajemen. Jakarta. Airlangga, Universtity. 2009. Pedoman Penulisan Pembimbingan dan Ujian Skripsi. Surabaya : Airlangga University Press.Al-Mubarakfuri, Shafiyyurrahman. 2010. Sirah Nabawiyah Cetakan ke-31. Jakarta Timur : Pustaka Al-Kautsar.Ali, Muhammad Daud. 1988. Sistem Ekonomi Islam Zakat dan Wakaf. Jakarta : UI-PressArifin, Zainul. 2006. Dasar Dasar Manajemen Bank Syariah. Jakarta : Pustaka Alvabet.A.Wahid.Sy. 2009. Fikih. Bandung : PT Armico.Badan Amil Zakat Nasional. 2016. Statistik Zakat Nasional 2016. Jakarta : BAZNAS.Baek, Irfan Syauqi; Siti Rahmawati; Ascarya. 2016. Merancang Manajemen Risiko Pengelolaan Zakat. Jakarta: Bank Indonesia.Bashori, Muhammad Anwar. 2017. Mendorong Pengembangan Islamic SOcial Finance dalam Rangka Mewujudkan Masyarakat Sejahtera. Makassar : Bank Indonesia.Basya, Muslim dan Irmulan Sati. 2006. Tantangan Indonesia Baru : Strategi dan Aktivitas Public Relations. Jakarta: Perhumas.Baqi, Muhammad Fuad bin Abdul. 2007. Hadist Shahih Bukhari Muslim. Jakarta : Fathan Publishing. Bungin, Burhan. 2008. Penelitian Kualitatif. Jakarta: Kencana.Carter dan Damcruz. 2013. Legal Risk Management Checklist for Not-For-Profit Organization. Carters Profesional Corporation. Clontz dan Heaven. 2015. Nonprofit Enterprise Risk Management : Best Practice and Case Studies.Cooper, Donald R. and Emory, C. William.. 1996. Metode Penelitian Bisnis,. Jakarta : Erlangga, Edisi Kelima.Cheese, Peter. 2016. Mananging Risk dan Building Resilent Organizations in Riskier  World. Emerald Insight , 324. Darmawi, Herman. 2005. Manajemen Risiko. Bumi Aksara, Jakarta. Departemen Agama, RI. 2012. Al-Qur'anulkariim. Jakarta : Cordoba Internasional Indonesia.Djojosoedarso, Soeisno, 2003. Prinsip-prinsip Manajemen Risiko Asuransi. Jakarta : Penerbit Salemba Empat.Dorfman. 1998. Introduction To Risk Management And Insurance. Edisi Keenam. Upper Saddle River, N.J. : Prentice Hall. Ernawati, Hasti. 2010. Zakat Sebagai Sarana Pengentasan kemiskinan (Studi Kasus. Di Lembaga Amil Zakat“Bina Umat Mandiri” kabupaten Ngawi). Jurnal. Skripsi. Malang : UIB MALANG. Fahmi, Irham. 2010. Manajemen Resiko. Bandung: Alfabeta.Faisal. 2011. Sejarah Pengelolaan Zakat di Dunia Muslim dan Indonesia (Pendekatan Teori Investigasi-Sejarah Charles Peirce dan Defisit Kebenaran Liven Boeve). Lampung : Jurnal IAIN Raden Intan Lampung (Analisis, Volome IX, Nomor 2, Desember 2011)Hakim Risal, Fathanul. 2015. Apa itu BAZ dan LAZ, Bagaimana Perilaku  Pemerintah terhadap BAZ dan LAZ. Kompsiana.com. Diakses pada 03 Juli 2017 pukul 10.06 WIB.Indonesia, Bank. 2016. Pengelolaan Zakat yang Efektif : Konsep dan Praktik di Beberapa Negara. Jakarta: Dep. Keuangan Syariah BI.Jatmiko, Wisnu; Ari Wibisono,dkk. 2014. Sisitem Informasi Zakat . Depok: UI Press.Karim, Adiwarman; Syaref, Azhar. 2009. Fenomena Unik di Balik Menjamurnya LAZ (Lembaga Amil Zakat) Di Indonesia. Jurnal Pemikiran dan Gagasan – Vol. I.Katsir, A.-H. I. 2012. Perjalanan Hidup Empat Khalifah Rasul yang Agung. Jakarta: Darul Haq.Matan, Ron; Hartnett, Bridget. 2011. How Non Profit Organizations Manage Risk.  Mubarok, Abdulloh; Fananni, Baihaqi. 2014. Penghimpunan Dana Zakat Nasional. Jurnal Permana - Vol. V.Nina Triyani, dkk. 2015. Analisis Manajemen Risiko. Jurnal Ekonomi Islam Republika .Okezone.com. 2015. Alasan Risma Bekukan Badan Amil Zakat. (https://news.okezone.com/read/2015/06/26/519/1172057/alasan-risma-bekukan-badan-amil-zakat diakses pada 14 Juni 2017 pukul 13.23)Patton, MQ. 2009. Metode Evaluasi Kualitatif. Jakarta: Pustaka Pelajar. PUSKASBAZNAS. 2016. Outlook Zakat Indonesia 2017. Jakarta: Pusat Kajian Strategis BAZNAS.Pusat Baznas Online. 2017. Daftar Pemenang BAZNAS Award dan Festival Zakat. (http://pusat.baznas.go.id/berita-utama/daftar-pemenang-baznas-award-dan-festival-zakat/ diakses pada 11 Juni 2017 pukul 18.34)Republika Online. 2015. Bekukan BAZ Surabaya, Pengamat Zakat Apresiasi Langkah Risma. (http://www.republika.co.id/berita/dunia-islam/wakaf/15/06/28/nqnu50-bekukan-baz-surabaya-pengamat-zakat-apresiasi-langkah-risma diakses pada 14 Juni 2017 pukul 08.17)Republik Indonesia. Undang-undang Nomor 23 tahun 2011 tentang Pengelolaan Zakat. 2011. www.djpp.kemenkumham.go.id Ridwan, Ahmad Hasan. 2011. Manajemen Zakat. Bandung : Humanity Publishing.Qardhawi, Yusuf. 2009. Halal dan Haram. Jakarta : Robbani Press.Salim, Abbas. 2007. Asuransi dan Manajemen Risiko. Jakarta: Raja Grafindo PersadaSoemirat, Soleh dan Elvinaro, Ardianto. 2008. Dasar-Dasar Public Relations. Bandung : PT. Remaja RosdakaryaSudirman. 2007. Zakat dalam Pusaran Arus Modernitas. Malang : UIN-Malang Press.Sugiyono. 2015. Metode Penelitian Kuantitatif, Kualitatif, dan R&D . Bandung: Alfabeta. Tampubolon, Robert. 2004. Manajemen Resiko Pendekatan Kualitatif untuk Bank. Jakarta: Elex Media Komputindo.Triani, Beik, dan Baga. 2015. Analisis Manajemen Risiko Pengelolaan Zakat. Jakarta : Jurnal Bank IndonesiaWibisono, Yusuf. 2013. Mengelola Zakat Indonesia. Jakarta : Kencana.Working Group of Zakat Core Principle. 2014. Towards an Establishment of an Efficient and Sound Zakat System.www.nurulhayat.org Yin, Robert K. 2013. Studi Kasus Desain & Metode. JAkarta : PT. Raja Grafindo Persada.